Studi Literatur Efektifitas Model Pembelajaran Problem Based Learning Dan Problem Solving Terhadap Kemampuan Berpikir Kritis Siswa Menengah Pertama - Pindy Komariyatin; Arifian Dimas (Universitas Sarjanawiyata Tamansiswa, 2022)
This article is structured to determine the effectiveness of Problem Based Learning and Problem Solving learning models on students' critical thinking skills. Data collection is done by collecting books and journals and then reading and reviewing them. After all the data was collected, testing and comparison of the effectiveness of the two learning models were carried out. The data analysis technique was carried out qualitatively by quoting the appropriate opinion. The results showed that the problem-based learning model is a very good model used in physics learning to improve students' critical thinking skills. This can be seen from the many learning theories that support the Problem Based Learning model and have succeeded in increasing critical thinking skills. Meanwhile, the Problem solving learning model has not been fully implemented optimally, because learning activities are still teacher centered. The successful application of the social system that has been implemented has not accommodated the improvement of critical thinking skills.